The international building challenge: a unique example of collaboration between European universities - Glen P. Stern; Natalia Borisovna Safronova; Kirill Borisovich Sivolapov (Недвижимость: экономика, управление, 2021)
The built environment is diverse in Europe. The establishment of a research group on “innovative real estate management” in 2010 marked the start of development of study programmes on the built environment at several universities in the Netherlands. The idea was to draft a game programme for students to compete for developing the best real estate design. Soon IBC became an international student exchange programme, allowing multidisciplinary student groups from different European cities to make the best propositions for a real estate case.